High prevalence of hospital-acquired infections caused by gram-negative carbapenem resistant strains in Vietnamese pediatric ICUs: A multi-centre point prevalence survey. Issue 27 (July 2016) - Le, Ngai Kien; HF, Wertheim; Vu, Phu Dinh; Khu, Dung Thi Khanh; Le, Hai Thanh; Hoang, Bich Thi Ngoc; Vo, Vu Thanh; Lam, Yen Minh; Vu, Dung Tien Viet; Nguyen, Thu Hoai; Thai, Tung Quang; Nilsson, Lennart E.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: There is scarce information regarding hospital-acquired infections (HAIs) among children in resource-constrained settings. This study aims to measure prevalence of HAIs in Vietnamese pediatric hospitals. Monthly point prevalence surveys (PPSs) in 6 pediatric intensive care units (ICUs) in 3 referral hospitals during 1 year. A total of 1363 cases (1143 children) were surveyed, 59.9% male, average age 11 months. Admission sources were: other hospital 49.3%, current hospital 36.5%, and community 15.3%. Reasons for admission were: infectious disease (66%), noninfectious (20.8%), and surgery/trauma (11.3%). Intubation rate was 47.8%, central venous catheter 29.4%, peripheral venous catheter 86.2%, urinary catheter 14.6%, and hemodialysis/filtration 1.7%. HAI was diagnosed in 33.1% of the cases: pneumonia (52.2%), septicemia (26.4%), surgical site infection (2%), and necrotizing enterocolitis (2%). Significant risk factors for HAI included age under 7 months, intubation and infection at admission. Microbiological findings were reported in 212 cases (43%) with 276 isolates: 50 Klebsiella pneumoniae, 46 Pseudomonas aeruginosa, and 39 Acinetobacter baumannii, with carbapenem resistance detected in 55%, 71%, and 65%, respectively. Staphylococcus aureus was cultured in 18 cases, with 81% methicillin - resistant Staphylococcus aureus . Most children (87.6%) received antibiotics, with an average of 1.6 antibiotics per case. Colistin was administered to 96 patients, 93% with HAI and 49% with culture confirmed carbapenem resistance. The high prevalence of HAI with carbapenem resistant gram-negative strains and common treatment with broad-spectrum antibiotics and colistin suggests that interventions are needed to prevent HAI and to optimize antibiotic use.